2015
DOI: 10.15263/jlmqa.2015.37.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Automated Chemiluminescence Assay for Antiphospholipid Antibody Testing

Abstract: Background: Detection of antiphospholipid antibodies (aPL) can be considered problematic due to assay variability and reagent sensitivity, high false-positive and false-negative rates, and lack of assay standardization. Therefore, utilizing an automated system can improve reproducibility and reduce interlaboratory variation. Here, we evaluated the analytical performance of the new automated ACL AcuStar chemiluminescence assay (Instrumentation Laboratory, USA). This was compared to the results of a panel analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…ELISA detection of aPL has been widely used domestically as well, although CLIA and FEIA methods have recently been introduced. 31,33 We also follow the revised international guidelines to monitor repeat positivities in Korea. 40,41 Several studies have shown that triple positivity correlates more strongly with both thrombosis and pregnancy morbidity than the presence of double or single positivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA detection of aPL has been widely used domestically as well, although CLIA and FEIA methods have recently been introduced. 31,33 We also follow the revised international guidelines to monitor repeat positivities in Korea. 40,41 Several studies have shown that triple positivity correlates more strongly with both thrombosis and pregnancy morbidity than the presence of double or single positivity.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Mostly aCL and aβ2GPI antibodies are measured by ELISA, although chemiluminescence (CLIA) and fluorescence enzyme immunoassays (FEIA) have recently been introduced to the market. 16,17,[27][28][29][30][31][32][33] In most of the cases, fair to moderate agreement was found among different assays. 16,17,29,[31][32][33] de Moerloose et al 28 observed far higher agreement between three well-established commercial assays.…”
Section: Anticardiolipin and Anti-β2 Glycoprotein-i Antibodiesmentioning
confidence: 89%
See 1 more Smart Citation